Perbedaan kepuasan perkawinan antara wanita yang mengalami infertilitas primer dan infertilitas sekunder - Nurul Hidayah; Noor Rochman Hadjam (HUMANITAS: Indonesian Psychological Journal, 2006)
The purpose of this research was to find out the difference of marital satisfaction between primary infertile female and secondary infertile female, with considering infertility stress. This research involved 50 infertile females, consist of 34 primary infertile females and 16 secondary infertile females. The subjects involved were patients at dr. Kasirun Kasim Putranto, Sp.OG’s Clinic (an obstetrician and gynecologist’s clinic).The data were obtained through Marital Satisfaction Scale, Infertility Stress Scale, and Infertility Questionnaire. Quantitative analytical test was done by application of SPSS version 12 software.The result of this research indicated that there was no significant differences of marital satisfaction between primary infertile female and secondary infertile female (F=0,341, p=0,562, p>0,05).